Role of the National Narcotics Agency of Bengkulu City in Prevent Drug Abuse - Kelzi Plaria Sari; Sumarto Widiono; Ika Pasca Himawati (Dinasti Publisher, 2025)
This research aims to analyze the role of the National Narcotics Agency of Bengkulu City in preventing drug abuse. The research method used is a qualitative approach with a qualitative descriptive research type. Data obtained through the of non-participant observation, interview, and documentation. Based on field data, the National Narcotics Agency of Bengkulu City has carried out its role and responsibility well to increase public awareness of the dangers of drugs, following the role of the National Narcotics Agency of Bengkulu City in preventing drug abuse includes: (1) Act as an extension of the government to become a socialization facilitator or extension on the impact of drug dangers and the negative effects caused by drug abuse. (2) Empowering the community to participate in carrying out drug abuse prevention activities in the surrounding area. (3) Play a role as a coordinator for the preparation of annual work plans in the prevention of drug abuse in carrying out coordination meetings with related agencies such as POLRI, Health Office and related institutions to prevent drug abuse in Bengkulu city.